Metabolic activation-driven mitochondrial hyperpolarization predicts insulin secretion in human pancreatic beta-cells - Gerencser, Akos A (Biochim Biophys Acta Bioenerg, 2018)
Mitochondrial metabolism plays a central role in insulin secretion in pancreatic beta-cells. Generation of protonmotive force and ATP synthesis from glucose-originated pyruvate are critical steps in the canonical pathway of glucose-stimulated insulin secretion. Mitochondrial metabolism is intertwined with pathways that are thought to amplify insulin secretion with mechanisms distinct from the canonical pathway, and the relative importance of these two pathways is controversial. Here I show that glucose-induced mitochondrial membrane potential (MMP) hyperpolarization is necessary for, and predicts, the rate of insulin secretion in primary cultured human beta-cells. When glucose concentration is elevated, increased metabolism results in a substantial MMP hyperpolarization, as well as in increased rates of ATP synthesis and turnover marked by faster cell respiration. Using modular kinetic analysis I explored what properties of cellular energy metabolism enable a large glucose-induced change in MMP in human beta-cells. I found that an ATP-dependent pathway activates glucose or substrate oxidation, acting as a positive feedback in energy metabolism. This activation mechanism is essential for concomitant fast respiration and high MMP, and for a high magnitude glucose-induced MMP hyperpolarization and therefore for insulin secretion.